An Evaluation of Service Quality of Banking, Identifying Its Priorities and Measures for Improvement - Saeid Saeida Ardakani; Seyyed Heidar Mirfakhraldini; Mohammad Zareian (‫مدیریت بازرگانی, 2009)
In recent years, banks must give more different and various services, because of maintaining of live and increasing their profitability. For the reason that high quality of services in attaining success is important, this question has propounded that how we can evaluate bank service quality. So, this research has performed with goal as evaluation of bank service quality in the agriculture bank. By spread Observation in literature, effective factors on bank service quality identified. Then customer's and clerk's view for importance of factors has attained. Being difference in opinion between customer's view and clerk's view about bank services, studied by using several statistic tests. Afterwards, suitable models used for evaluating service quality of bank. Results show that, there is meaningful difference between customer's view and clerk's view about importance of effective factors on bank service quality. Moreover, statistic tests and analysis show meaningful difference between customer's view and clerk's view about state of services. According to research results, "Speed in giving needed services to customers" and "giving services of bank in promised time" have identified as most necessary criteria to be improved.